Long-Term Behavior of Solutions of the Difference Equation 𝑥𝑛+1=𝑥𝑛−1𝑥𝑛−2−1 - Candace M. Kent; Witold Kosmala; Stevo Stević (Abstract and Applied Analysis)
We investigate the long-term behavior of solutions of the following difference equation: 𝑥𝑛+1=𝑥𝑛−1𝑥𝑛−2−1, 𝑛∈ℕ0, where the initial values 𝑥−2, 𝑥−1, and 𝑥0 are real numbers. Numerous fascinating properties of the solutions of the equation are presented.